Uji Kepekaan Bakteri Yang Diisolasi Dari Urin Penderita Infeksi Saluran Kemih (ISK) Terhadap Beberapa Antibiotika Pada Periode Maret–Juni 2008 - Kumala, Shirly; Raisa, Nancy; Rahayu, Lestari; Kiranasari, Ariyani (UI Scholars Hub, 2009)
Urinary tract infections (UTI) was an inflammatory response of the urethra when attacked by microorganisms. This disease can happen to people at all ages beginning with asymptomatic to moderately symptomatic infections. Thus far, antibiotic treat-ment was the best for curing the UTI although the chances for being resistance to the antibiotics were also high. Resistance to gram negative bacteri,a in particular, often occur with the antibiotics treatment. Our study at the Faculty of Medicine, University of Indonesia (UI), Bacterial isolation from patient urine sample was performed in the microbiology laboratory of UI. A total of 50 urine samples were collected from X patients volunteered in our study for bacterial isolation, however, only 23 bacterial isolates were successfully obtained. Study was carried out to moni-tor the susceptibility of bacterial isolate towards several types of antibiotics (ofloksazim, amoxyicillin, fosfomisin and sefepim) using Cakram disffusion method. Study re-sults demonstrated that susceptibility of oflokazim to both gram positive and nega-tive bacteria was very low while amoxycillin showed desecding trend of efficacy towards all types of bacteria. Fosfomisin and sefepim, on the other hand, demon-strated strong susceptibility to both gram positive and negative bacteria found in the isolates. Furthermore, it is very interesting to observe ofloksazim was resistant to gram postivie and negative bacteria. Collectively, these research findings strongly illustrated the susceptibility patten and resistance scale of baterial isolates towards various antibiotic tested in the study.